Mikroprosesor intel : 8086/8088, 80286/80288, 80286, 80386, 80486, Pentium Pro, dan Pentium II: arsitektur, pemrograma, antarmuka - Brey, Barry B. (Erlangga, 2002)
Judul asli:THe Intel microprosesor. rnJilid: 1